2017
DOI: 10.1016/j.linged.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating learning in early childhood: Narratives from migrant homes

Abstract: The study investigates how parents of Polish ethnic background, resettled in Norway, reflect on their children's learning in Norwegian early years educational institutions through 19 qualitative interviews. With narratives of experience as the main theoretical and analytical vantage point, their negotiations of positioning towards the Norwegian educational practice are explored in the narrative worlds they construct, in the interactional context of the interview and in the wider socio-cultural contexts. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, Multicultural pedagogy can help children develop a more nuanced awareness of diverse cultures and perspectives, improving their social and emotional development (34). In addition, multicultural pedagogy can help children develop a sense of cultural identity and pride in their own culture, which can also contribute to their social development (34,36,37). Also, multicultural teaching helps children appreciate others and comprehend how varied cultural backgrounds affect communication and social interaction by understanding and integrating multiple cultural concepts and experiences (29)(30)(31)33,36).…”
Section: Discussionmentioning
confidence: 99%
“…However, Multicultural pedagogy can help children develop a more nuanced awareness of diverse cultures and perspectives, improving their social and emotional development (34). In addition, multicultural pedagogy can help children develop a sense of cultural identity and pride in their own culture, which can also contribute to their social development (34,36,37). Also, multicultural teaching helps children appreciate others and comprehend how varied cultural backgrounds affect communication and social interaction by understanding and integrating multiple cultural concepts and experiences (29)(30)(31)33,36).…”
Section: Discussionmentioning
confidence: 99%
“…This has an impact on the establishment of meaningful links with schools. Other studies found that institutional barriers and stereotypical assumptions are some of the factors inhibiting the establishment of meaningful connections and consequently impact on children's life chances (Bubikova-Moan, 2017;Hamilton, 2013). Therefore it is crucial for institutions to understand migrant families within the context of the layers of influence that shape them and not perpetuate deficit views.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description, as well as an extensive analysis of the data set, has been presented elsewhere (Bubikova-Moan 2017a, 2017b, 2019. It is nonetheless of special note here that the interview participants are primarily labour migrants to Norway and hence explicitly or implicitly implicated in the wider societal discourse on migration.…”
Section: Preliminary Methodical Notes On the Empirical Datamentioning
confidence: 99%